Results of pelvic and para-aortic lymph nodes dissection surgery in early ovarian cancer - Ha, Hoang Thanh; Xuan, Nguyen Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Objective: This study aims to explore the characteristics of stage I ovarian cancer, and the surgical outcomes of pelvic and para-aortic lymph nodes (PLN and PALN) dissection. Methods: A prospective descriptive study was conducted on 34 patients with stage I ovarian cancer from January/ 2018 to March /2021 who underwent PLN and PALN dissection surgery in Danang Oncology Hospital. These patients were followed up for 12 months. Results: The average age was 48.8 ± 2.3 years old (22 - 75). Symptoms were abdominal pain at 86.8% and urinary disorders at 36.9%. Almost tumors were moved in clinical: 87.1%. Ultrasound found the mixture tumor in 67.7% (MRI: 85.3%), papillae in the tumor was 93.5%, and wall in tumors was 35.5%. The average tumor size was 123.6 ± 16.4 mm (36 - 180). 38.7% of them had increased CA125. The average number of pelvic and para-aortic lymph nodes was 11.5 and 8.1, respectively. There was 1 case with a positive pelvic lymph node and 3 cases with positive para-aortic LN. After surgery, there were 4 cases diagnosed to stage III, accounting for 11.8%. The average surgery time was 188.6 minutes, the average blood loss was 238 ml, and the postoperative in-patient time was 8.9 days. The complications of this operation were found out and well dealt with. There were no recurrent cases at the 6 months postoperation. At 12 months, 1 case had Ca125 > 100 U/ml but no symptom and evidence recurrent on MRI and CT. All patients were alive. Conclusion: Pelvic and para-aortic lymph nodes dissection are highly applicable, safe, and acceptable complications, with impressive DFS and OS, and should be performed routinely in oncology centers which appropriate human resources.